An Economic Analysis Of High Efficiency Irrigation System For The Farmers Of Pakistan - Muhammad Akram Yaqoob , Sher Muhammad , Ejaz Ashraf , Muhammad Rizwan Amjad; Muhammed Arshad (Migration Letters, 2024)
Water is the most precious resource, vitally important for sustainable agriculture. Pakistan is among the utmost vulnerable states to water scarcity. Scarce resource the water is depleting due to inefficient irrigation methods. This challenging situation demands to conserve precious water and ensure its efficient use. Therefore, Pakistan is immediately required to improve its irrigation efficiency and water productivity by introducing modern sustainable irrigation technology . This study examine theeconomic analysis of high-efficiency irrigation system (HEIS) and water productivity in southern Punjab, Pakistan.Multi-stage sampling is used to select the sample of 400 farmers (200 HEIS adopters & 200 non-adopters) from major districts of south Punjab.Benefit cost ratio (BCR) values for wheat, guava and citrus using SI and DI are found to be larger than 1.The SI system’s net present value (NPV) values for the wheat crop ranged from Rs. 248034 to Rs.[1] 463191. Similarly, the results are consistent for DI for guava and citrus orchards . (BCR>1 and NPV positive values demonstrate that HEIS project is more economically feasible and viable than TI). Moreover, the benefit-cost ratio demonstrated that, when compared to conventional irrigated farms, the yield of citrus, wheat, and guava due to HEIS improved significantly to 48.48%, 70% and 44.83% respectively. Water productivity of HEIS-irrigated wheat, guava and citrus were calculated as 1.2 kg/m3, 2.6 kg/m3 and 2.5 kg/m3 respectively which increased highly significantly than TI. The findings suggested that government initiatives should focus to enhance adoption rate of HEIS to increase water productivity aimed poor farmers prosperity. This could be accomplished by providing modest subsidized HEIS, improving education, engaging young ones in farming and imparting awareness to farmers about the socioeconomic benefits of HEIS.